2006
DOI: 10.1002/jgt.20211
|View full text |Cite
|
Sign up to set email alerts
|

Nowhere‐zero flows in tensor product of graphs

Abstract: Abstract:In this paper, we characterize graphs whose tensor product admit nowhere-zero 3-flow. The main result is: For two graphs G 1 and G 2 with δ G 1 ≥ 2 and G 2 not belonging to a well-characterized class of graphs, the tensor product of G 1 and G 2 admits a nowhere-zero 3-flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In [10] it is shown that the direct product of nontrivial graphs admits an NZ 3-flow if one factor does not have any leafs and the other is not a member of a certain family of trees.…”
Section: Introductionmentioning
confidence: 99%
“…In [10] it is shown that the direct product of nontrivial graphs admits an NZ 3-flow if one factor does not have any leafs and the other is not a member of a certain family of trees.…”
Section: Introductionmentioning
confidence: 99%
“…was investigated by Zhang et al [17] and Imrich et al [4], respectively. More results on nowhere-zero 3-flows and group connectivity of products of graphs can be found in [9,15,16] and others.…”
Section: Introductionmentioning
confidence: 99%
“…The 3-flow conjecture has received somewhat less attention. Perhaps the lack of progress in this area has motivated several authors to examine flow numbers of graphs resulting from various graph operations, most notably graph products [5], [6], [10], [12], [15], [20]. Very recently Thomassen proved the 3-flow conjecture for 8-edge-connected graphs [17].…”
Section: Introductionmentioning
confidence: 99%